Nosological Differences in the Nature of Punctate White Matter Lesions in Preterm Infants - Malova, Mariya; Morelli, Elena; Cardiello, Valentina; Tortora, Domenico; Severino, Mariasavina; Calevo, Maria Grazia; Parodi, Alessandro; De Angelis, Laura Costanza; Minghetti, Diego; Rossi, Andrea; Ramenghi, Luca Antonio (Frontiers in Neurology, 2021)
Background: The pathogenesis of punctuate white matter lesions (PWMLs), a mild form of white matter damage observed in preterm infants, is still a matter of debate. Susceptibility-weighted imaging (SWI) allows to differentiate PWMLs based on the presence (SWI+) or absence (SWI–) of hemosiderin, but little is known about the significance of this distinction. This retrospective study aimed to compare neuroradiological and clinical characteristics of SWI+ and SWI– PWMLs. Materials and methods: MR images of all VLBW infants scanned consecutively at term-equivalent age between April 2012 and May 2018 were retrospectively reviewed, and infants with PWMLs defined as small areas of high T1 and/or low T2 signal in the periventricular white matter were selected and included in the study. Each lesion was analyzed separately and characterized by localization, organization pattern, and distance from the lateral ventricle. Clinical data were retrieved from the department database. Results: A total of 517 PWMLs were registered in 81 patients, with 93 lesions (18%) visible on SWI (SWI+), revealing the presence of hemosiderin deposits. On univariate analysis, compared to SWI- PWML, SWI+ lesions were closer to the ventricle wall, more frequently organized in linear pattern and associated with lower birth weight, lower gestational age, lower admission temperature, need for intubation, and presence of GMH-IVH. On multivariate analysis, closer distance to the ventricle wall on axial scan and lower birth weight were associated with visibility of PMWLs on SWI (p=0.003 and p=0.0001, respectively). Conclusions: Our results suggest a nosological difference between SWI+ and SWI− PWMLs. Other prospective studies are warranted to corroborate these observations.